Scar nonexcitability using simultaneous pacing for substrate ablation of ventricular tachycardia. Issue 11 (6th August 2020) - Anderson, Robert D.; Lee, Geoffrey; Campbell, Timothy; Bennett, Richard G.; Kizana, Eddy; Watts, Troy; Kalman, Jonathan; Kumar, Saurabh
Abstract: Objectives: To describe an expedited strategy of simultaneous high‐output pacing during radiofrequency ablation to achieve scar homogenization and electrical inexcitability as an approach for substrate ablation for scar‐related ventricular tachycardia (VT). Background: Scar homogenization with additional testing for electrical inexcitability is known endpoints for catheter ablation, but achieving both can be time consuming. We describe a strategy of simultaneous pacing during radiofrequency ablation to expedite this approach. Methods and results: Ten patients (age 74 ± 6 years; all men, (LV) ejection fraction of 33% ± 8%, ischemic cardiomyopathy, 9; VT storm, 7) underwent scar homogenization with electrical inexcitability to pacing (10 mA, 9 ms pulse width), as well as noninducibility of any VT as an acute procedural endpoint. Thirty‐four VTs were inducible in 10 patients with a total of 1127 ablation lesions applied. Median ablation lesions per patient were 97 (interquartile range [IQR]25‐75 71‐151), and the total ablation time was 49 minutes (IQR25‐75 45‐56 minutes) with average duration per lesion of 32.2 seconds (IQR25‐75 25.8‐37.8 seconds). Average power was 33 W (IQR25‐75 32‐38 W), average contact force was 13 g (IQR25‐75 11.9‐14.6 g) with a median impedance drop of 9.6 Ω/lesion (IQR25‐75 8.1‐10.0 Ω). There were no ventricular fibrillation episodes using this strategy. The median procedure time was 246 minutes (IQR25‐75 214‐293 minutes). Acute procedural success was seen in nine patients with 97% of VTs noninducible. Conclusion: Simultaneous ablation with high output pacing to achieve scar inexcitability, when combined with scar homogenization and noninducibility of any VT may be an expeditious, safe, and effective technique for catheter ablation.